Multidimensional ultrasound and computed tomography imaging support in bleeding plexiform neurofibromatosis of the scalp: A case report and literature review - Ximena Wortsman; Nelson Lobos; Rodrigo De la Parra; Laura Carreno (Wolters Kluwer Medknow Publications, 2015)
Active bleeding in plexiform neurofibromatosis can be a life-threatening complication in neurofibromatosis type 1 (NF1). The prompt imaging support of 2D-3D ultrasound (US) and computed tomography (CT) during the active hemorrhage phase of cutaneous neurofibromas has not been previously reported. We report a case with NF1 who experienced a sudden swelling in the parieto-temporal region that corresponded to a massive and active hemorrhage within a plexiform neurofibroma. The US and CT imaging characteristics of this bleeding tumor are shown. Active hemorrhage in a plexiform neurofibroma of the scalp appeared in US as a heterogeneous hypodermal mass. CT demonstrated a fully hyperdense soft tissue mass. These characteristics differ from the non-complicated or old hemorrhagic imaging appearances of scalp plexiform neurofibromas and encourage prompt surgical treatment. This case report demonstrates the usefulness of imaging support in the early diagnosis of this hemorrhagic complication of NF1 in the scalp and also stimulates multispecialty management.